Description of Stress Level of Diabetes Mellitus Patients with Hyperglycemia - Yeyen; Dewi Rachmawati; Tri Cahyo Sepdianto (Journal of Ners and Midwifery, 2026)
Diabetes mellitus with hyperglycemia is a concern because it can cause short-term and long-term complications. Ineffective stress management can affect the difficulty of controlling blood sugar levels. The purpose of this study was to describe of the stress level of diabetes mellitus patients with hyperglycemia. The research design method used a quantitative descriptive, with a purposive sampling technique and the total sample 39 respondents with inclusion criteria, namely that patients with hyperglycemia with their blood sugar levels ≥ 250 mg/dl and accompanied by comorbidities such as stroke, Chronic Kidney Disease (CKD), or acute coronary syndrome. The data collection instrument used is DASS−42 questionnaire sheet consists of 14 stress statement with a total of 42 questions with indicator difficulties in relaxing, nerve passion, and easily sad or agitation, and impatience. 0 assessment if yo never, score 1 if sometimes, score 2 if often, score 3 if always. The results were grouped when the normal stress was: 0−14, mild stress: 15−18, moderate stress: 19−25, severe stress: 26−33, dan very hard: >34. Based on the results showed that 48.72% (19 people) had a moderate stress level category, mild stress of 33.33% (13 people), severe stress of 12.82% (5 people) and normal stress of 5.13% (2 people). Based on the results of this study, factors that cause moderate stress levels due to age factors, prolonged 1−5 years, and irregular treatment.